(untitled) (Estudios Gerenciales, 2017)
This study aims at analyzing the relationship between determinant factors of disclosure of information on environmental impacts of Brazilian companies. A descriptive, documental and quantitative research was conducted through a sample of 97 Brazilian companies. In the Sustainability Reports and in the Annual Reports information, five environmental aspects were collected: emissions, effluents, wastes, products and services; and transport, which were used to measure the degree of environmental disclosure. This concludes that there is a relationship between the variables investigated in all analyzed years. The size, audit and Global Reporting Initiative (GRI) are associated with disclosure and the Corporate Sustainability Index (CSI), Pollution Potential (POTEN), governance, stocks, Return on Assets (ROA) and Return on Equity (ROE) are not